Challenges to parental involvement in children’s education at a primary school: a rasch analysis - Badrasawi, Kamal J I; Yahefu, Humaer; Khalid, Madihah (IIUM Press, 2020)
Literature has evidenced the positive significant role of parental involvement in children’s personality development and education. However, research on parental involvement in children’s education is sparse in rural areas, especially among ethnic minorities in China. Hence, a research project was conducted to examine the level of parental involvement and its role in influencing children’s academic achievement in these areas; and to identify the challenges to parental involvement. This paper aimed to identify the challenges to parental involvement using the cross-sectional survey design. The parents’ of Grades Three and Four school children were selected to answer a questionnaire on parental involvement. The items on challenges to parental involvement were analyzed using the Rasch Measurement Model (Winsteps software program, version 4.1.0). The Rasch analyses revealed that the research instrument met the measurement requirements. Parents’ low proficiency in the Chinese language and the complexity of the school subjects were the biggest challenges to parental involvement. This research has provided useful information to parents, teachers, school administration and policy makers. Further research could be conducted using more items and larger samples from other school grades. Qualitative research is recommended to obtain more in-depth information on parental involvement in general, and the challenges in particular.